Comments on Federated's Acquisition and Bankruptcy: Lessons and Implications - Christopher G. Lamoureux (Washington University Law Quarterly, 1994)
This Article is a case study of Campeau Corporation's acquisition of Federated Department Stores in 1988, Federated's subsequent bankruptcy filing, and finally its emergence from Chapter 11 in 1992.
Keywords: Macy' s Inc.; Acquisitions and mergers; Bankruptcy law; United States; Steven N. Kaplan; Valuation; Bankruptcy reorganization